The Role of Aeromonas hydrophila in Diarrhea - MM Aslani; MY Alikhani (Tehran University of Medical Sciences, 2004)
Aeromonas hydrophila is a causative agent of a number of human infections. Aeromonads have been isolated from patients with diarrhea. In spite of a number of virulence factors produced by Aeromonas species, their association with diarrheal diseases has not been clearly linked. In current study, 1546 fecal samples of a randomly selected population were screened for presence of A. hydrophila. Out of the total number of cases, 20 were suffering from diarrhoea and the rest were asymptomatic healthy individuals. The result showed that 3.4% of the samples were positive for Aeromonas spp. A. hydrophila was isolated as the sole enteropathogen from 80% diarrheal and 20% asymptomatic cases. A significant association was found between the A. hydrophila and diarrhoeal diseases in rural and urban areas (P<0.05), while no difference was revealed between genders. The highest rates of A.hydrophila (3.9%) was detected in children <6 years of age. A significant association was also found between A. hydrophila and different age groups (P< 0.05). In conclusion, our epidemiological study showed that Aeromonas spp. as a sole enteropathogen could be responsible for diarrhea.